Knowledge discovery, knowledge engineering and knowledge management : 7th International Joint Conference, IC3K 2015, Lisbon, Portugal, November 12-14, 2015, Revised selected papers /: 7th International Joint Conference, IC3K 2015, Lisbon, Portugal, November 12-14, 2015, Revised selected papers. (2016) - Unknown
No abstract available